Pembilang Acuan Dan Pemeriksaan Bentuk (Die Counter And Shape Inspection) - Mat Nawang, Bazli (Universiti Sains Malaysia, 2006)
Image processing is a new area in the world. It is develop parallel with developement technology in computer system. Nowadays, there are many area involve in image processing and that make image processing is important part in daily life. For simple example is to recover deblurring image, adding conspicuous effect to the image, adjusting size of the image and many more. Image processing usually has been used in important area such as medical which is used to process X-ray image. X-ray image usually blurred and it need to recover for further process. Image processing also usually important in geology and astronomy. The main objective of this project is to deblurring image and counter the total of dice on wafer. The input image is wafer image which deblurred by space and lense degredation. So, the purpose of this project is to recover the input image and the result should be nearly same with the original image. There are many software can be use to process image like MATLAB, JAVA, Boland C++ and many more. For this project, the software has been choosen is MATLAB 7.0. This is because their advantages like their toolboxes which has basic command in using this software.